Long non-coding RNA MSTO2P promotes the proliferation and colony formation in gastric cancer by indirectly regulating miR-335 expression - Han Li; Hua Zhu; Yanbing Zhou; Haibo Wang; Zhaojian Niu; Yi Shen; Liang Lv (Tumor Biology, 2017)
Long non-coding RNAs are emerging as new players in gene regulation, but whether long non-coding RNAs influence the expression of microRNA is unclear. The expression levels of misato family member 2, pseudogene were significantly associated with lymphatic metastasis and distal metastasis in 80 paired gastric cancer tissues using real-time quantitative reverse transcription polymerase chain reaction experiments. The effects of long non-coding RNA misato family member 2, pseudogene were assessed by overexpressing or downexpressing long non-coding RNA misato family member 2, pseudogene in gastric cancer cells. Long non-coding RNA misato family member 2, pseudogene promoted gastric cancer cell growth, colony formation, migration, and invasion in gastric cancer cells. Long non-coding RNA misato family member 2, pseudogene influenced biologic functions in gastric cancer cells via indirectly regulating the activation of miR-335. Our results reveal long non-coding RNA misato family member 2, pseudogene as an oncogenic long non-coding RNA that promotes cell growth and invasion. Therefore, long non-coding RNAs might function as key regulatory hubs in gastric cancer progression.